Answer:
(A): Using the equations of motion, we can determine the answer as follows:

formula (3) is obtained from (1) and (2), using equation (3) the answer is determined as below:
![\begin{gathered} y(x)=xtan(\theta)-(g)/(2(v_(\circ))^2cos^2(\theta))x^2 \\ \\ v_(\circ)=22\text{ f/s} \\ \\ \theta=45 \\ \\ g=32.1522\text{ f/s} \\ \\ y(x)=xtan(45)-(32.1522)/(2*22^2cos^2(45))x^2 \\ \\ y(x)=x-(32.1522)/(2*22^2cos^2(45))x^2 \\ \\ y(x)=x-(32.152,2)/(484)x^2 \\ \\ y(x)=x-0.06643x^2 \\ \\ (x,y)\rightarrow\text{ Adjusting the position for the shift gives:} \\ \\ y(x)=[(x+10)-0.06643(x+10)^2]+6\rightarrow(4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/aryq65jfz177f59pmea72d2j9xk7l0pi91.png)
The plot of the (4) reveals the following:
Therefore the answer is no.
(D) Trying a new angle theta = 60 degrees gives the following new answer:
Therefore the answer is:
